Analisis Sikap Ibu Hamil Terhadap Penggunaan Buku Kesehatan Ibu dan Anak di Puskesmas Minasa Upa Kota Makassar - Ningsi, Agustina; Mukarramah, Sitti; Sabur, Fitriati; Nurfadilah, Nurfadilah (Jurnal Kebidanan Malakbi, 2023)
Infant health status, nutritional status is one of the things that affect the health status of a country. The indicators for choosing a child's health degree include the Infant Mortality Rate (IMR), the purpose of this study is to find out the attitude of pregnant women to the use of the Maternal Child Health (MCH) handbook at the Minasa Upa Health Center. This type of research design uses cross sectional (cross sectional) and the dependent variable is the attitude of pregnant women while the independent variable is the use of the MCH handbook, measurements were taken at the same time with 35 respondents. Data collection using a questionnaire. then data analysis used the Chi Square Test with the result that the value of P = 0.000 > from α = 0.05 then the alternative hypothesis (Ha) is accepted meaning that there is a correlation between pregnant women's attitudes towards the use of maternal and child health books at the Minasa Upa Health Center in 2021.